An Up-To-Date Overview of Dental Tissue Regeneration Using Dental Origin Mesenchymal Stem Cells: Challenges and Road Ahead - Wang, Lin-Hong; Gao, Si-Zhe; Bai, Xiao-Lei; Chen, Zheng-Lin; Yang, Fan (Frontiers in Bioengineering and Biotechnology, 2022)
Stem cells (SCs) research has experienced exponential growth in recent years. SC-based treatments can enhance the lives of people suffering from cardiac ischemia, Alzheimer’s disease, and regenerative drug conditions, like bone or loss of teeth. Numerous kinds of progenitor/SCs have been hypothesized to depend on their potential to regain and/or heal wounded tissue and partly recover organ function. Growing data suggest that SCs (SCs) are concentrated in functions and that particular tissues have more SCs. Dental tissues, in particular, are considered a significant cause of mesenchymal stem cells (MSCs) cells appropriate for tissue regeneration uses. Tissue regeneration and SCs biology have particular attention in dentistry because they may give a novel method for creating clinical material and/or tissue redevelopment. Dental pulp, dental papilla, periodontal ligament, and dental follicle contain mesenchymal SCs. Such SCs, which must be identified and cultivated in specific tissue culture environments, may be used in tissue engineering applications such as tooth tissue, nerve regeneration, and bone redevelopment. A new cause of SCs, induced pluripotent SCs, was successfully made from human somatic cells, enabling the generation of the patient and disease-specific SCs. The dental SC’s (DSCs) multipotency, rapid proliferation rate, and accessibility make it an ideal basis of MSC for tissue redevelopment. This article discusses current advances in tooth SC investigation and its possible application in tissue redevelopment.